Factors influencing survival in patients with multidrug-resistant Acinetobacter baumannii infection - Prata-Rocha,Mariana Lima (2012)
Multidrug-resistant (MDR) Acinetobacter baumannii (Acb) is a rapidly emerging pathogen in healthcare settings. The aim of this study was to evaluate the predictors of poor outcome in patients with MDR Acb. This is the first report documenting factors influencing survival in patients with MDR Acb in this tertiary hospital. This study is a prospective of the hospital epidemiology database. A total of 73 patients with 84 Acb isolates were obtained between August 2009 and October 2010 in this hospital. In the present study, the 30-day mortality rate was 39.7%. Of 84 Acb isolates, 50 (59%) were MDR, nine (11%) were pan-resistant, and 25 (30%) were non-MDR. The non-MDR isolates were used as the control group. The factors significantly associated with multidrug resistance included previous surgeries, presence of comorbidity (renal disease), use of more than two devices, parenteral nutrition, and inappropriate antimicrobial therapy. Significant predictors of 30-day mortality in the univariate analysis included pneumonia, diabetes mellitus, renal disease, use of more than two devices, and inappropriate antimicrobial therapy administered within two days of the onset of infection. The factors associated with mortality in patients with MDR Acb infection in this study were: age > 60 years, pneumonia, diabetes mellitus, renal disease, use of more than two invasive procedures, and inappropriate antimicrobial therapy. Vigilance is needed to prevent outbreaks of this opportunistic and deadly pathogen.